High-velocity plasma spray process using hybrid SiO2 + ZrO2 precursor for deposition of environmental barrier coatings - Miranda, F. S.; Caliari, F. R.; Campos, T. M.; Leite, D. M.G.; Pessoa, R. S.; Essiptchouk, A. M. [UNESP]; Petraconi, G. (Elsevier, 2020)
The demand for the development of more efficient, low emission, and high-performance aircraft have required new methods to obtain lighter materials, with higher temperature resistance and chemical stability. For these purposes, Environmental Barrier Coatings (EBC) are largely studied. EBC's are commonly obtained through Atmospheric Plasma Spray, where the process parameters, as well as the precursor characteristics, and its interaction with the plasma jet influence the properties of the deposited material. In this context, this work aims to deposit EBC on C/C composites through the high-velocity plasma spray (HVPS) using a new concept of hybrid SiO2 + ZrO2 precursor. For this, a solid load of 7% yttria-stabilized zirconia (7YSZ) is mixed in a Si(OH4) solution with concentrations of 10, 20, and 30 g/L. From Raman and XRD analyses, ZrSiO4 and SiC were identified, its formations occur due to the reactions of SiO2 with ZrO2 (7YSZ) and the SiO2 precursor with C/C substrate. Finally, we demonstrate the versatility of the HVPS process using a hybrid precursor, capable of producing micro/nanostructured EBC coatings.
Keywords: Environmental barrier coating; High-velocity plasma spray; Material characterization; Silicon oxide; Yttria-stabilized zirconia